PERBEDAAN KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DAN TEAMS GAMES TOURNAMENT TERHADAP PRESTASI BELAJAR IPS DI SEKOLAH DASAR MBS KABUPATEN BANTUL YOGYAKARTA - Maisaroh, Siti; Purwanti, Rosalia Susila (Jurnal Penelitian Pendidikan, 2012)
This study is aimed to understand whether there are differences of studentâs study achievement between the usage of jigsaw cooperative study model with the usage of team games tournament (TGT) study model, also to understand which one is more effective between both of two in the progress of studentâs study achievement development. This research is quasi experiment. Free variable in the research is jigsaw cooperative study model and teams games tournament and as the bond variable is studentâs study achievement. The population in the research are all of grade IV students of MBS Elementary School of Bantul Regency Year of Study 2010/2011, sample that used are grade IV students of Kembang Putihan Elementary School, Guwosari Elementary School and Sungapan Elementary School. In the research, there is 2 experiment class namely Jigsaw class which is treated with cooperative study of jigsaw and team games tournament (TGT) class which is treated with cooperative study of team games tournament (TGT). Method that used in the data obtaining are documentation, test, and observation, whereas data analysis uses t-test. The result of the research shows that cooperative jigsaw study model is more effective compared with the cooperative team games tournament (TGT) study model. It is shown with calculated t as much as 2,196 larger than t-table = 1,99 for a = 5%, it means there is study achievementâs differences between cooperative jigsaw study model with cooperative team games tournament (TGT) study at grade IV students of year of study 2010/2011. in the other side, based on the study achievement score of the students, it is shown that cooperative jigsaw study model have ability to give better studentâs study achievement score with average score 80,82 higher than the usage of cooperative team games tournament (TGT) study model that is 75,05